Statistical mechanics - Huang, Kerson. (John Wiley and Sons, 1987)
The laws of thermodynamics. Some applications of thermodynamics. The problem of kinetic theory. The equilibrium state of a dilute gas. Transport phenomena. Classical statistical mechanics.